Analisis Pengaruh Electronic Word of Mouth, Brand Image, Brand Trust terhadap Keputusan Pembelian pada Marketplace Shopee - Herniati Herniati; Erik Sudarso; Tina Warsiningsih; Sigit Tri Hartono; Elita Darmasari (Jurnal Syntax Admiration, 2024)
This study aims to analyse the effect of Electronic Word of Mouth (e-WOM), brand image, and brand trust on purchasing decisions at the Shopee marketplace. The research method used is quantitative. Data was collected through questionnaires distributed to 100 Shopee users in Indonesia. The results of the analysis show that e-WOM, brand image, and brand trust have a positive and significant influence on purchasing decisions. Of the three variables, brand trust has the most dominant influence in shaping consumer decisions to make purchases. This research provides implications that Shopee needs to increase consumer trust and strengthen brand image to drive purchasing decisions through effective digital marketing strategies.